Investigating The Effect of IFRS Implementation on Accounting Information Relevance - Mulyadi, Nanda Pramayasti; Maharani, Neni; Valdiansyah, Riyan Harbi (Universitas Jakarta Internasional, 2024)
The primary objective of this study is to evaluate the impact of International Financial Reporting Standards (IFRS) on the value of accounting information, as this metric serves as the predominant benchmark for a company's financial statements. This study employs a literature review methodology to compare pre- and post-IFRS implementation values in Indonesia against an understanding of accounting information value from existing companies. The findings of this study indicate that IFRS adoption does not significantly alter the value of accounting information in Indonesia. The implementation of IFRS principles is unlikely to induce substantial changes in countries such as Indonesia, which operates within a legal system that is unable to provide investors with adequate safeguards for secure investments. This situation is further exacerbated by the limited capacity of the legal function in these countries, particularly in the context of the predominant role of banks. The influence of global factors on the value of accounting information, particularly in Indonesia, further compounded these challenges.